Slowly Digestible Carbohydrate Diet Ameliorates Hyperglycemia and Hyperlipidemia in High-Fat Diet/Streptozocin-Induced Diabetic Mice - Chen, Yu-Zhong; Gu, Jia; Chuang, Wei-Ting; Du, Ya-Fang; Zhang, Lin; Lu, Meng-Lan; Xu, Jia-Ying; Li, Hao-Qiu; Liu, Yan; Feng, Hao-Tian; Li, Yun-Hong; Qin, Li-Qiang (Frontiers in Nutrition, 2022)
Objective: Given that the prevalence rate of type 2 diabetes mellitus (T2DM) continues to increase, it is important to find an effective method to prevent or treat this disease. Previous studies have shown that dietary intervention with a slowly digestible carbohydrate (SDC) diet can improve T2DM with almost no side effects. However, the underlying mechanisms of SDC protect against T2DM remains to be elucidated. Methods: The T2DM mice model was established with a high-fat diet and streptozocin injection. Then, SDC was administered for 6 weeks. Bodyweight, food intake, organ indices, fasting blood glucose (FBG), oral glucose tolerance test (OGTT), homeostasis model assessment for insulin resistance (HOMA-IR), and other biochemical parameters were measured. Histopathological and lipid accumulation analyses were performed, and the glucose metabolism-related gene expressions in the liver and skeletal muscle were determined. Lastly, colonic microbiota was also analyzed. Results: SDC intervention alleviated the weight loss in the pancreas, lowered blood glucose and glycosylated hemoglobin levels, and improved glucose tolerance and HOMA-IR. SDC intervention improved serum lipid profile, adipocytokines levels, and lowered the lipid accumulation in the liver, subcutaneous adipose tissue, and epididymal visceral adipose tissue. In addition, SDC intervention increased the expression levels of IRS-2 and GLUT-2 in liver tissues and elevated GLUT-4 expression levels in skeletal muscle tissues. Notably, SDC intervention decreased the Bacteroidetes/Firmicutes ratio, increased Desulfovibrio and Lachnospiraceae genus levels, and inhibited the relative abundance of potentially pathogenic bacteria. Conclusions: SDC intervention can improve hyperglycemia and hyperlipidemia status in diabetic mice, suggesting that this intervention might be beneficial for T2DM.